Veering : a theory of literature - Royle, Nicholas, 1957- (Frontiers of theory., 2011)
Reflections on the figure of veering form the basis for a new theory of literature. Exploring images of swerving, loss of control, digressing and deviating, Veering provides new critical perspectives on all major literary genres: the novel, poetry, drama, the short story and the essay, as well as 'creative writing'. Royle works with insights from Lewis Carroll, Freud, Adorno, Raymond Williams, Edward Said, Deleuze, Cixous and Derrida. With wit and irony he investigates 'veering' in the writings of Jonson, Milton, Dryden, Wordsworth, Coleridge, Melville, Hardy, Proust, Lawrence, Bowen, J.H. Prynne and many others. Contrary to a widespread sense that literature has become increasingly irrelevant to our culture and everyday life, Royle brilliantly traces a strange but compelling 'literary turn'.